[OP.2A.06] QUANTIFICATION OF URINARY PROTEIN LEVELS OF PODOCYTE ASSOCIATED MOLECULES IN HYPERTENSIVE PATIENTS WITH MICROALBUMINURIA. (September 2017) - Perez-Hernandez, J.; Olivares, D.; Solaz, E.; Pichler, G.; Chaves, F.; Cortes, R.; Redon, J.
Abstract : Objective: Microalbuminuria is an indicator of early renal and vascular disorders. Decrease in podocyte number is a critical determinant contributing to the development of proteinuria. We hypothesize that urinary protein levels of podocyte-associated molecules could be related with an early glomerular injury. Thus, the objective of this study was to quantify the protein and mRNA levels of podocalixyn and nephrin in urinary sediment of hypertensive patients with microalbuminuria. Design and method: This prospective study analyzed 21 hypertensive patients with microalbuminuria (12 men and 9 women, mean age 52.7 ± 6.4 years), and 31 hypertensive patients without microalbuminuria (21 men and 10 women, mean age 53.2 ± 7.4 years). We quantified mRNA and protein levels of podocyte-associated molecules (podocalixyn and nephrin), and aquaporin-1, as renal tubular control, by quantitative PCR and immunoblot in the urinary sediment of these patients. Then, we correlated urinary protein levels with clinical parameters. Results: Urinary protein levels of podocalyxin and nephrin were significantly augmented in microalbuminuric group compared to normalbuminuric [3.0-fold change, p < 0.001; and 2.7-fold change, p < 0.001, respectively). Whereas, mRNA levels of nephrin showed a significant decrease (2.9-fold change, p < 0.01) and podocalixyn mRNA values were similar in microalbuminuric patients. Aquaporin-1 values were not different between groups. Podocalixyn and nephrin protein levels were correlated with mRNA expression in microalbuminuric patients (r = 0.53, p < 0.01, and r = 0.74, p < 0.001, respectively). Furthermore, urinary podocalixyn and nephrin protein levels were associated with urinary protein/creatinine levels in microalbuminuric patients (r = 0.74, p < 0.01; and r = 0.68, p < 0.05, respectively). Finally, mRNA nephrin levels were also correlated significantly with urinary protein/creatinine ratio (r = 0.73, p < 0.05). Conclusions: Protein levels of podocyte associated molecules are higher in urinary sediment of hypertensive patients with microalbuminuria and mRNA expression were diminished, indicating a podocyte damage. Urinary podocalyxin and nephrin are correlated with clinical parameters such as proteinuria. Protein levels of podocyte associated molecules could be a valuable method for studying an early glomerular injury in these patients.